2022
DOI: 10.1080/21655979.2021.2020394
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Achyranthes bidentata components in reducing inflammatory response through Arachidonic acid pathway for treatment of Osteoarthritis

Abstract: Achyranthes bidentate is a common traditional Chinese medicine (TCM) used in treating osteoarthritis (OA). The compatibility between effective components has now become a breakthrough in understanding the mechanism of TCM. This study aimed at determining the optimal compatibility and possible mechanism of Achyranthes bidentate for OA treatment. Results showed that the adhesion score of the OA group is higher than NC group, and showed a trend of down-regulation in the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Arachidonic acid metabolites were able to inhibit cell proliferation in the inflamed synovium, thereby limiting arthritis inflammation and pannus formation. 50 , 51 The enrichment of GPXs in the arachidonic acid metabolic pathway suggested that GPXs may reduce the inflammatory response to OA treatment through the arachidonic acid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Arachidonic acid metabolites were able to inhibit cell proliferation in the inflamed synovium, thereby limiting arthritis inflammation and pannus formation. 50 , 51 The enrichment of GPXs in the arachidonic acid metabolic pathway suggested that GPXs may reduce the inflammatory response to OA treatment through the arachidonic acid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The staining procedure for hematoxylin and eosin (H&E) was performed following the established protocol described in previous publications [ 16 ]. Briefly, ovarian tissues fixed with 4% paraformaldehyde (Servicebio, China) were dehydrated, embedded, and sectioned (The maximum transverse section of the ovary wasserially sliced into 4 μm sections).…”
Section: Methodsmentioning
confidence: 99%
“…From week 6 after modeling, the normal and model groups were given normal saline at a dose of 10 ml/(kg·day), whereas the ABPS group was given a clinically equivalent dose of ABPS at 400 mg/(kg·day) ( 20 ). Almost all previous studies opted for the oral intake method for ABPS for treating bone diseases, such as osteoporosis ( 12 , 20 , 21 ) and OA ( 13 ). Since the present study was focused on exploring the protective mechanism of ABPS against OA, the most common delivery method, which is the oral gavage, was adopted for the rats.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical structure of ABPS is dominated by furan rings, where its molecular weight is in the range of 1.4-3.4 kDa ( 11 ). ABPS has been widely applied for the treatment of bone-related diseases, such as osteoporosis and OA, due to its observed protective effects on the bone ( 12 , 13 ). As an anti-inflammatory agent, ABPS has been previously shown to interfere with the inflammatory activation that occurs during OA and the metabolic pathway of arachidonic acid ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation